Diversity of dinoflagellates in the Northern Vietnam coastal waters - Chu, Van Thuoc; Nguyen, Thi Minh Huyen; Duong, Thanh Nghi; Nguyen, Ngoc Lam (Vietnam Journal of Marine Science and Technology, 2025)
Phytoplankton were investigated within the framework of the Vietnam’s coastal water quality monitoring program. The present study analyzed phytoplankton samples collected in the northern Vietnam coastal waters (Tra Co, Cua Luc, Do Son, Ba Lat, Sam Son and Cua Lo stations) from 2019 to 2022 to characterize diversity and abundance of dinoflagellate communities. A total of 129 species belonging to 35 genera, 23 families, 8 orders, and 2 classes of dinoflagellates were recorded in this study area. The diversity of dinoflagellates varied depending on the sampling locations and times. Tripos furca was recorded as the most dominant and common species (accounting for approx. 93% of the samples) in the dinoflagellate communities throughout the year. The density of dinoflagellates and Tripos furca varied strongly by sampling locations, times, and tides. This species seems preferable and grows with high density in the study area from June to September. Among water environment factors, salinity had the strongest correlation with the density of Tripos furca depending on the sampling locations and the tides.